Effectiveness of Physical Exercise and Diet in Heart Failure Patients: A Literature Review - Berna Detha Meilyana; Nikma Alfi Rosida; Ekwantoro Ekwantoro; Sutiyo Dani Saputro; Ratih Ayu Puspasari (Critical Medical and Surgical Nursing Journal (CMSNJ), 2022)
Introduction: Heart failure is a pathological condition in which the heart's organs no longer have the ability to pump blood to the ventricles and throughout the body. One of the leading causes of morbidity and mortality is heart failure. Functional capacity and patient quality of life are correlated in patients with heart failure. Exercise and diet can be used to increase functional capacity. This study aimed to identify the effectiveness of exercise and diet as treatment modalities to improve patient well-being and quality of life outcomes. Methods: This article employs the evidence-based practice of physical exercise (exercise) and a comprehensive diet for heart failure as part of a literature review methodology. Journal articles that meet the requirement of 12 were included in this article. While articles that are inappropriate or only abstract did not include in this study. Result: Twelve articles were included in the study. The suggested physical activity, such as walking, can be completed in 6 minutes or 30 minutes over a week, three times. And a 30-minute riding session is possible. The DASH diet is advised, and patients should receive the recommended amount of sodium (1500 mg/day). Conclusion: Physical exercise and a comprehensive diet that can be done well in heart failure patients can help patients reduce the risk of developing symptoms that can trigger the severity of heart failure. Moreover, patients can carry out daily activities and do their jobs well, and improve their quality of life.